Electronic properties of topological insulator candidate CaAgAs - Nayak, Jayita; Kumar, Nitesh; Wu, Shu-Chun; Shekhar, Chandra; Fink, Joerg; Rienks, Emile D. L.; Fecher, Gerhard H.; Sun, Yan; Felser, Claudia (Journal of Physics: Condensed Matter, 2018)
The topological phases of matter provide the opportunity to observe many exotic properties, such as the existence of 2D topological surface states in the form of Dirac cones in topological insulators and chiral transport through the open Fermi arc in Weyl semimetals. However, these properties affect the transport characteristics and, therefore, may be useful for applications only if the topological phenomena occur near the Fermi level. CaAgAs is a promising candidate for which the ab initio calculations predict line-nodes at the Fermi energy. However, the compound transforms into a topological insulator on considering spin-orbit interaction. In this study, we investigated the electronic structure of CaAgAs with angle-resolved photoemission spectroscopy (ARPES), ab initio calculations, and transport measurements. The results from ARPES show that the bulk valence band crosses the Fermi energy at the Γ-point. The measured band dispersion matches the ab initio calculations closely when shifting the Fermi energy in the calculations by -0.5 eV. The ARPES results are in good agreement with transport measurements, which show abundant p-type carriers.
CRIS-Team Scopus Importer:2022-04-14
Keywords: angle-resolved photoemission spectroscopy; electrical transport; electronic structure; topological insulator